Supradapedon revisited: geological explorations in the Triassic of southern Tanzania - Langer, Max C.; Rosa, Atila A. S. da; Montefeltro, Felipe C. [UNESP] (Peerj Inc, 2017)
The upper Triassic deposits of the Selous Basin in south Tanzania have not been prospected for fossil tetrapods since the middle of last century, when Gordon M. Stockley collected two rhynchosaur bone fragments from the so called Tunduru beds''. Here we present the results of a field trip conducted in July 2015 to the vicinities of Tunduru and Msamara, Ruvuma Region, Tanzania, in search for similar remains. Even if unsuccessful in terms of fossil discoveries, the geological mapping conducted during the trip improved our knowledge of the deposition systems of the southern margin of the Selous Basin during the Triassic, allowing tentative correlations to its central part and to neighbouring basins. Moreover, we reviewed the fossil material previously collected by Gordon M. Stockley, confirming that the remains correspond to a valid species, Supradapedon stockleyi, which was incorporated into a comprehensive phylogeny of rhynchosaurs and found to represent an Hyperodapedontinae with a set of mostly plesiomorphic traits for the group. Data gathered form the revision and phylogenetic placement of Su. stockleyi helps understanding the acquisition of the typical dental traits of Late Triassic rhynchosaurs, corroborating the potential of hyperodapedontines as index fossils of the Carnian-earliest Norian.
Keywords: Rhynchosauria; Supradapedon; Triassic; Selous basin; Tanzania; Tunduru; Carnian